Community-developed checklists for publishing images and image analyses - Schmied, Christopher; Nelson, Michael S.; Avilov, Sergiy; Bakker, Gert-Jan; Bertocchi, Cristina; Bischof, Johanna; Böhm, Ulrike; Brocher, Jan; Carvalho, Mariana T.; Chiritescu, Catalin; Christopher, Jana; Cimini, Beth A.; et al. (Nature methods, 2024)
Images document scientific discoveries and are prevalent in modern biomedical research. Microscopy imaging in particular is currently undergoing rapid technological advancements. However, for scientists wishing to publish obtained images and image-analysis results, there are currently no unified guidelines for best practices. Consequently, microscopy images and image data in publications may be unclear or difficult to interpret. Here, we present community-developed checklists for preparing light microscopy images and describing image analyses for publications. These checklists offer authors, readers and publishers key recommendations for image formatting and annotation, color selection, data availability and reporting image-analysis workflows. The goal of our guidelines is to increase the clarity and reproducibility of image figures and thereby to heighten the quality and explanatory power of microscopy data.